2022
DOI: 10.1007/s40120-022-00350-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health Outcomes of Lecanemab in Patients with Early Alzheimer’s Disease Using Simulation Modeling

Abstract: Introduction Alzheimer’s disease (AD) is a progressive, neurodegenerative disease and is the most common cause of dementia. Lecanemab is a humanized monoclonal antibody targeting amyloid protofibrils for the treatment of early AD. In the phase II BAN2401-G000-201 trial (NCT01767311), lecanemab reduced amyloid accumulated in the brain and slowed progression on key global and cognitive scales evaluating efficacy after 18 months of treatment. Methods A disease simulation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…It is anticipated that approval of lecanemab would restrict its use to patients in the early stages of Alzheimer's disease [14]. They account for around 2 million of the total 6 million patients diagnosed with the condition [16].…”
Section: Resultsmentioning
confidence: 99%
“…It is anticipated that approval of lecanemab would restrict its use to patients in the early stages of Alzheimer's disease [14]. They account for around 2 million of the total 6 million patients diagnosed with the condition [16].…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have been reported that anti-Aβ protofibril antibody lecanemab has produced modest but highly statistically significant results in a trial. The drug met its primary endpoint of slowing cognitive decline in individuals with mild cognitive impairment (MCI), a clinical presentation thought to be a precursor to AD, and those with mild AD ( 32 , 33 ).…”
Section: Pathogenesis Of Admentioning
confidence: 99%
“…Drugs that improve the symptoms have been used in such cases to suppress exacerbation and delay the progression of cognitive dysfunction. Recently, new amyloid disease modifiers that control progression have been developed 2–4 . The first step in diagnosing cognitive dysfunction is to identify mild cognitive impairment (MCI) or the cognitively normal (CN) before the onset of AD, and then begin the treatment accordingly 4–6 …”
Section: Introductionmentioning
confidence: 99%